An outbreak of kerato-conjunctivitis among corralled, supplementary fed, semi-domestic reindeer calves - Rehbinder, Claes; Nilsson, Anna (Rangifer, 1995)
The winter 1993-94 was hard with periods of severe cold and a thick, snow layer. In the beginning of January 1994, approximately 500 reindeer calves were separated from the main herd and corralled for supplementary feeding. During this period around 30 calves died by emaciation and other circumstances related to the change in feeding regimes. Fourteen days later, the calves were rounded up, lassoed and transported around 50 km to another corral. The animals, under severe stress and underfed were offered an insufficiently pelleted feed. After two days, some animals showed signs of eye irritation and on the third and fourth days, several calves had developed unilateral or bilateral kerato-conjunctivitis and blindness. The remaining 390 calves, were slaughtered at the end of January. During the time spent in the second corral, around 80 calves died by emaciation, some of them were blind. Around 300 calves were then, or had been, affected. Of these about 240 were unilaterally blind and 60 bilaterally blind. Bacteriological, virological, electron-microscopical and histopathological investigations showed that fodder particles in the conjunctival sac caused the primary lesions which were secondarily invaded by opportunistic bacteria. The stressful situation of the calves may have contributed to the severity and the rapid development of the lesions.